The Incentive Properties of Collective Reputation - Pierre Fleckinger; Wanda Mimra; Angelo Zago (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We build a model of collective reputation under moral hazard to analyze incentives under collective reputation. Producers can produce high quality, but it is only imperfectly detected. Products not detected as of high quality are pooled by to the collective reputation structure. Collective reputation can yield higher quality and welfare than individual reputation. While groups unravel in absence of transfers even when efficient, simple collective reputation contracts implement the First Best.
Keywords: D82; D47; D71; L15; 330